Enhancing Resilience to Turbulent Global Financial Markets: An Indonesian Experience - Sri Mulyani Indrawati; Ndiame Diop; Mohamad Ikhsan; Febrio Kacaribu (Institute for Economic and Social Research, 2020)
In the empirical literature, large and abrupt declines in capital inflows, or sudden stops, typically hit asset markets and generate output losses in the receiving countries. The significant decrease in capital flows to emerging markets in 2018 is a unique opportunity to test this premise. Using Indonesian data, we found that the sharp decline in capital inflows for over two consecutive quarters in 2018 had an adverse impact on the currency, equities, and bond markets, but no discernible output loss was recorded. Real GDP growth remained resilient throughout 2018 and held broadly steady at around 5 percent in the first quarter of 2019. Furthermore, asset markets rebounded quickly, regaining most of the losses incurred by March 2019. We attribute this resilience to Indonesia’s strong macroeconomic fundamentals and responsive fiscal and monetary policies. We argue that to sustain this resilience in the years to come, complementary structural reforms to boost export-oriented FDI would be needed. The 2020 COVID-19 global pandemic has put the emerging economies to the test again, with a possibly more significant impact. We will revisit our analysis in the future in the aftermath of the pandemic.